2011
DOI: 10.1111/j.1365-2362.2011.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased gene expression of LC3 in peripheral leucocytes of patients with coronary artery disease

Abstract: LC3 gene expression in the peripheral leucocytes was significantly decreased in patients with CAD, indicating that autophagosome formation is decreased. These data suggest that autophagy in circulating leucocytes may be involved in the pathogenesis of atherosclerosis and CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Autophagy markers were assessed in CD4 lymphocytes of males subjected to different exercise regimens or sedentary controls after 5 weeks of training; they found that exercise conditioning (especially high intensity interval training) triggers autophagy and suppresses apoptosis in lymphocytes when the subjects undergo a hypoxic exercise challenge 94 . The authors did not go so far as to suggest that the autophagic response in lymphocytes might reliably report on autophagy in other organs, but two studies by another group found a significant reduction in autophagy markers (by western blotting) in leukocytes of patients with coronary artery disease 95 or acute myocardial infarction 96 compared to healthy controls. However, none of these studies correlated autophagy markers in lymphocytes with those in heart tissue, so it remains to be seen whether peripheral blood cells represent a reliable reflection of autophagic activity in the heart.…”
Section: Methods To Measure Autophagy and Mitophagymentioning
confidence: 99%
“…Autophagy markers were assessed in CD4 lymphocytes of males subjected to different exercise regimens or sedentary controls after 5 weeks of training; they found that exercise conditioning (especially high intensity interval training) triggers autophagy and suppresses apoptosis in lymphocytes when the subjects undergo a hypoxic exercise challenge 94 . The authors did not go so far as to suggest that the autophagic response in lymphocytes might reliably report on autophagy in other organs, but two studies by another group found a significant reduction in autophagy markers (by western blotting) in leukocytes of patients with coronary artery disease 95 or acute myocardial infarction 96 compared to healthy controls. However, none of these studies correlated autophagy markers in lymphocytes with those in heart tissue, so it remains to be seen whether peripheral blood cells represent a reliable reflection of autophagic activity in the heart.…”
Section: Methods To Measure Autophagy and Mitophagymentioning
confidence: 99%
“…Lower levels of LC3-II (measured by Western blot) were observed in peripheral blood leukocytes in patients with coronary artery disease compared to age and sex-matched healthy controls 24 of peripheral blood lymphocytes with intracellular staining of membrane-associated LC3 25 . A number of commercial kits for this purpose are now available.…”
Section: Clinically Feasible Approaches To Monitoring Autophagymentioning
confidence: 94%
“…We have previously reported altered LC3 gene expression levels in CAD and AMI patients [21]. Several genetic variants have been identified in the ATG7 and LC3 gene in AMI patients [22,23].…”
Section: Introductionmentioning
confidence: 92%